ANALISIS PROSES REKRUITMEN CALON LEGISLATIF PEREMPUAN DALAM PEMILU LEGISLATIF 2014 KOTA SEMARANG (STUDI KASUS PADA PARTAI PERSATUAN PEMBANGUNAN) - Atmaja Hadi, M. Reza; ., Fitriyah; ., kushandajani (Journal of Politic and Government Studies, 2014)
In legislative election many political parties faces the some problem, theexistence of female representation. The existence of 30% quota system and zyppersystem makes all political parties focusing on preparing their femalerepresentative even more.In this research, the writer used qualitative method which focuse onrecruitment of female representative in DPC PPP in Semarang. The result ofshows that the recruitment by DPC PPP in Semarang resulting femalerepresentative who are not to join the election itself.DPC PPP in Semarang is one of the representative of legislative election2014 in Semarang City. To prepare its female legislative representative DPC PPPin Semarang has already held a recruitment which is followed by its femalerepresentatives. The result of the recruitment is DPC PPP in Semarang can fulfillboth rules mentioned before in legislative election 2014.Most of them join the elections because of the encouragement frompolitical parties staffs. In this year election, DPC PPP in Semarang itselft lacks offemale representative. Therefore, political staffs encourages its femalerepresentative to join the legislative election 2014. The recruitment process forfemale representative done by DPC PPP in Semarang can make this partiessuccesfully join in election. But in fact, these female representatives are only usedas shield by the parties to face both systems.2Key words : Female Representative, 30% Quota System, Zypper System andRecruitment of Female Legislative Representative